Mastering professional scrum : a practitioner's guide to overcoming challenges and maximizing the benefits of agility - Ockerman, Stephanie; Reindl, Simon (Professional scrum series., 2019)
"Our job as Scrum professionals is to continually improve our ability to use Scrum to deliver products and services that help customers achieve valuable outcomes. This book will help you to improve your ability to apply Scrum."--The Foreword by Ken Schwaber, co-author of Scrum Mastering Professional Scrum is for anyone who wants to deliver increased value by using Scrum more effectively. Leading Scrum practitioners Stephanie Ockerman and Simon Reindl draw on years of Scrum training and coaching to help you return to first principles and apply Scrum with the professionalism required to achieve its transformative potential. The authors aim to help you focus on proven Scrum approaches for improving quality, getting and using fast feedback, and becoming more adaptable, instead of "going through the motions" and settling for only modest improvements. Whether you're a Scrum Master, Development Team member, or Product Owner, you'll find practical advice for facing challenges with transparency and courage, overcoming a wide array of common challenges, and continually improving your Scrum practice. Realistically assess your current Scrum practice, and identify areas for improvement Recognize what a great Scrum Team looks like and get there Focus on "Done"--not "sort-of-Done" or "almost-Done" Measure and optimize the value delivered by every Product Increment Improve the way you plan, develop, and grow Clear away wider organizational impediments to agility and professionalism Overcome common misconceptions that stand in the way of progress Register your book for convenient access to downloads, updates, and/or corrections as they become available. See inside book for details